PENGARUH PENAMBAHAN TEPUNG UMBI PORANG (Amorphophallus oncophyllus) SEBAGAI PREBIOTIK PADA RANSUM BROILER TERHADAP BOBOT DAN PANJANG USUS HALUS: Effect of Addition Porang Tuber Flour (Amorphophallus oncophyllus) as Prebiotick on Broiler Feed Against Intestinal Weight and Length - . Annisa; A. Mujnisa; Daryatmo Daryatmo (Buletin Nutrisi dan Makanan Ternak, 2021)
Porang Tubers (Amorphophallus oncophillus) contain glucomannan which functions as a prebiotic that can affect the performance and condition of the broiler digestive tract which has an impact on broiler performance. This study aimed to determine the effect of adding elephant foot yam tuber flour (Amorphophallus oncophyllus) to the feed on the weight and length of the small intestine. The parameters observed were the weight and length of the small intestine. The design used was a completely randomized design (CRD) which consisted of P0 (basal ration without porang flour), P1 (Ration + porang flour 0.4%), P2 (Ration + porang flour 0.8%), and P3 (Ration + porang flour 1.2%). The treatment was carried out for 35 days starting from the beginning of maintenance. Gastrointestinal tract weight and length were measured when the broilers were 35 days old. The results showed that the P1 treatment had a significant effect (P<0.05) on the weight of the duodenum (0.79 ± 0.09) and the length of the ileum (9.29 ± 1.10) but had no significant effect on the weight of the jejunum (1.79 ± 0.34), Ileum (1.48 ± 0.22) and length of Duodenum (3.21 ± 0.55), Jejunum (8.17 ± 1.08). Based on the results of the research that has been carried out, it can be concluded that the addition of elephant foot yam tuber flour to a level of 1.2% does not have a negative effect on the length and weight of the small intestine. Keywords: Porang Flour, Duodenum, Jejunum, Ileum, and Small Intestine.